Adsorbents for Water and Wastewater Treatment and Resource Recovery - Santos, Sílvia; Botelho, Cidália; Pintor, Ariana (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Adsorption is a well-established operation used for water decontamination and the remediation of industrial effluents. It is also recognized as a key technology for recovering substances of economic interest or those at risk of scarcity. The new sustainability paradigm of the circular economy and the current context of promoting the efficient use of natural resources, water and energy have been motivating the search for eco-friendly adsorbents for water and wastewater treatment and resource recovery. This Special Issue compiles 21 papers (17 research articles and 4 reviews), addressing the removal of heavy metals, toxic metalloids, precious metals and organics from aqueous solution, using a wide variety of adsorbents derived from natural and waste materials.